Improve the quality of card services at techcombank – lang ha branch = Nâng cao chất lượng dịch vụ thẻ tại ngân hàng TMCP Kỹ Thương - Chi nhánh Láng Hạ - Nguyễn, Thị Ngọc Anh (2020)
Researching basic theoretical issues about the quality of commercial bank card services. Clarify analysis of the current status of card usage of the Bank. Give some suggestions and solutions to improve the card usage quality of the Bank. Proposing some recommendations to the Government, State Bank and Association of card issue and payment banks in Vietnam. Practical applicability, if any: Is a document that helps Techcombank - Lang Ha branch to refer to in the process of researching to improve the quality of using your bank's card.